Phytochemicals as Potential Epidrugs in Type 2 Diabetes Mellitus - Ramírez-Alarcón, Karina; Victoriano, Montserrat; Mardones, Lorena; Villagran, Marcelo; Al-Harrasi, Ahmed; Al-Rawahi, Ahmed; Cruz-Martins, Natália; Sharifi-Rad, Javad; Martorell, Miquel (Frontiers in Endocrinology, 2021)
Type 2 diabetes Mellitus (T2DM) prevalence has significantly increased worldwide in recent years due to population age, obesity, and modern sedentary lifestyles, with future estimates indicating that 439 million people will be diabetic in 2030. Characterized by an impaired β-pancreatic cell function and insulin secretion, hyperglycemia and insulin resistance, more recently the epigenetic regulation of β-pancreatic cells differentiation has been underlined as being involved in T2DM development. It is currently known that several bioactive molecules, widely abundant in plants used as food or infusions, have a key role in histone modification and DNA methylation. These epigenetic modifications have made them potential epidrugs candidates against T2DM. In this sense, epigenetic mechanisms involved in T2DM and protein targets will be reviewed, with special focus in studies addressing the potential use of phytochemicals as epidrugs that prevent and/or control T2DM in vivo and in vitro. As main findings, and although some controversial results have been found, bioactive molecules with epigenetic regulatory function, appear to be a potential replacement/complementary therapy of pharmacological hypoglycemic drugs, with minimal side effects. Indeed, natural epidrugs have shown to prevent or delay the T2DM development and the morbidity associated to dysfunction of blood vessels, eyes and kidneys due to sustained hyperglycemia in T2DM patients.